2007
DOI: 10.1016/j.bbrc.2006.11.093
|View full text |Cite
|
Sign up to set email alerts
|

Junctin is a prominent regulator of contractility in cardiomyocytes

Abstract: Junctin is one of the components of the ryanodine receptor Ca release channel complex in sarcoplasmic reticulum. To determine the role of acute alteration of junctin protein levels on cardiomyocyte contractility, we used adenoviral-mediated gene transfer techniques in adult rat cardiomyocytes. Acute downregulation of junctin by 40% resulted in significant increases in cell shortening, rate of contraction (+dL/dt) and rate of relaxation (-dL/dt). The alteration of contractile parameters was associated with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…This effect may explain the reduced SR Ca load and the lower Ca spark frequency in junctin-overexpressing mice (18). In line with these findings, overexpression of junctin in isolated myocytes was associated with a prolonged relaxation (9,10). In contrast, the deletion of junctin was accompanied by a higher SR Ca content and a hastened relaxation in knockout mice (45).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This effect may explain the reduced SR Ca load and the lower Ca spark frequency in junctin-overexpressing mice (18). In line with these findings, overexpression of junctin in isolated myocytes was associated with a prolonged relaxation (9,10). In contrast, the deletion of junctin was accompanied by a higher SR Ca content and a hastened relaxation in knockout mice (45).…”
Section: Discussionsupporting
confidence: 70%
“…In contrast, the overexpression of triadin in single-transgenic mice was associated with a 73% downregulation of junctin, limiting the interpretation of physiological alterations, which were thus ascribed directly to triadin. Moreover, the separate investigation of both models is stringently necessary because recent studies have revealed new insight into the important role of junctin in regulating SR Ca homeostasis and contractility (9,10,45). Thus characterization of the present co-overexpression model allowed a more precise definition of triadin function in SR Ca signaling.…”
Section: Discussionmentioning
confidence: 94%
“…Changes in expression of other proteins (Kirchhefer et al, 2003, Hong et al, 2002) as well as in the cardiac t-tubule/SR junction (Franzini-Armstrong et al, 2005) must also impact on Ca 2+ release. An inhibitory effect of junctin on cardiac RyR2 channels is also indicated by enhanced Ca 2+ release in cardiac myocytes from junctin knock-down mice (Yuan et al, 2007) and with acute down-regulation (Fan et al, 2007) although both knockdown and overexpression can also induce changes in expression levels of other proteins (Wang et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Rat ventricular myocytes were isolated from adult male Sprague-Dawley rats (6–8-wk old) and plated on laminin-coated glass coverslips or dishes, as described previously [24]. Recombinant adenoviruses Ad.GFP encoding GFP, Ad.Hsp20 containing both Hsp20 and GFP, and Ad.Hsp20-AS containing both antisense Hsp20 and GFP were generated by using the AdEasy-1 expression system, as described previously [21, 22].…”
Section: Methodsmentioning
confidence: 99%